Effect of metacarpophalangeal joint position on A1 pulley and flexor digitorum tendons in trigger digit. Issue 10 (October 2019) - Wu, Tung-Tai; Wu, Po-Ting; Lee, Su-Ya; Wu, Kuo-Chen; Shao, Chung-Jung; Chern, Tai-Chang; Su, Fong-Chin; Jou, I-Ming
Abstract : Background: The aim of this study was to evaluate and compare the cross-sectional area (CSA) of flexor digitorum tendons and the thickness of first annular (A1) pulleys between contralateral normal digits and trigger digits (TDs) at positions of finger flexion and extension using a noninvasive ultrasound system. Methods: Seventeen affected fingers of 17 patients (6 men and 11 women) with TDs in one hand, and 17 contralateral normal digits without trigger finger symptoms were examined. The sonographic appearances of flexor digitorum tendons and A1 pulleys were observed at two positions of metacarpophalangeal (MCP) joint flexion: 0° and 60°. Results: The findings of this study indicate that CSA of flexor digitorum tendons and A1 pulley thickness were significantly larger in both positions of 0° and 60° flexion of MCP joint compared with contralateral normal digits ( p < 0.01). In TDs, there was a significantly thicker A1 pulley at 60° flexion of MCP joint than that at 0° flexion ( p < 0.01), but no significant change on CSA of flexor tendons. Conclusion: Our results suggested that TDs lead to the thicker A1 pulley and larger CSA of the flexor digitorum tendons. The mismatch in volume change between CSA of flexor digitorum tendons and A1 pulley thickness during MCP flexion may lead to the trigger phenomenon.